D-Psicose mitigates NAFLD mice induced by a high-fat diet by reducing lipid accumulation, inflammation, and oxidative stress - Tan, Jiajun; Sun, Wen; Dong, Xueyun; He, Jiayuan; Ali, Asmaa; Chen, Min; Zhang, Leilei; Wu, Liang; Shao, Keke (Frontiers in Nutrition, 2025)
D-Psicose (DPS) serves as an optimal sucrose substitute, providing only 0.3% of sucrose’s energy content, while exhibiting anti-inflammatory properties and inhibiting lipid synthesis. However, its efficacy in managing non-alcoholic fatty liver disease (NAFLD) remains unclear. This study employed network pharmacology and molecular docking to identify potential DPS targets for NAFLD treatment. A high-fat diet was used to induce a NAFLD mouse model, with DPS administered in drinking water at 5% (high dose DPS group, DPSH group) and 2.5% (low dose DPS group, DPSL group) concentrations. After 12 weeks, blood lipid levels, liver lipid deposition, and inflammation were evaluated to assess the therapeutic effects of DPS. To explore its underlying mechanisms, colon contents 16S rRNA sequencing and serum untargeted metabolomics were performed. Results indicated that DPS significantly reduced lipid accumulation and inflammatory damage in the livers of NAFLD mice, improving both blood lipid profiles and oxidative stress. Network pharmacology analysis revealed that DPS primarily targets pathways associated with inflammation and oxidative stress, while molecular docking suggested its potential to inhibit the NF-κB pathway activation and the expression of the receptor for advanced glycation end-products (RAGE), findings corroborated by Western blotting. Additionally, gut microbiota and serum metabolomics analyses demonstrated that DPS improved microbiota composition by increasing the abundance of beneficial bacteria, such as Akkermansia, and restored serum metabolomic balance, enhancing anti-inflammatory and antioxidant metabolites like Tretinoin and Pyridoxamine. The non-targeted metabolomics results suggest that DPS is mediated by glutathione metabolism, arginine and proline metabolism, unsaturated fatty acid biosynthesis, and linoleic acid metabolism interferes with NAFLD progression. In conclusion, DPS may alleviate oxidative stress and lipid accumulation in NAFLD mice through the AGEs/RAGE/NF-κB pathway, while also ameliorating gut microbiota dysbiosis and serum metabolomic disturbances, fostering the production of anti-inflammatory and antioxidant metabolites.